Treatment of postoperative wounds using pectin-based reinforced dressings and their antimicrobial activity - Vlizlo, V.; Mysak, A.; Stybel, V.; Voloshyn, R.; Leno, Yu. et. al. (ЛНУВМ та БТ імені С. З. Ґжицького, 2021)
A reinforced pectin-based dressing with a reinforcing element containing the antimicrobial agent chlorhexidine bigluconate has been developed. In vitro studies have shown that the hydrogel pectin dressing containing 0.03 ÷ 1.5 % chlorhexidine bigluconate inhibits the growth of both gram-positive (S. aureus) and gram-negative (P. aeruginosa) bacteria.
Keywords: postoperative wounds; dressings; hydrogel; antimicrobial activity; chlorhexidine; післяопераційні рани; армовані пов'язоки; пектин